UJI EFEKTIVITAS SEDIAAN SABUN CAIR PEMBERSIH KEWANITAAN YANG MENGANDUNG EKSTRAK DAUN TANJUNG (Mimusp elengy L) TERHADAP PERTUMBUHAN Candida albicans - Rusmin Rusmin (Akademi Farmasi Yamasi Makassar, 2022)
This study aims to determine the effectiveness of liquid feminine cleansing soap containing tanjung leaf extract (Mimusops elengi L) and the most effective concentration. The type of research used is experimental research which is a laboratory research using a simple experimental design, namely the effectiveness of antifungal liquid soap for feminine cleansing tanjung leaf extract (Mimusp elengy L) against Candida albicans. This research will be carried out in July 2019 at the Laboratory of Pharmaceutical Microbiology, Laboratory of Pharmaceutical Technology and Pharmacy Phytemy, Faculty of Pharmacy, University of Pancasakti, Makassar. The results of statistical analysis using a completely randomized design method (ANAVA) showed that giving negative control of tanjung leaf extract and Resik V liquid soap as a comparison gave a significantly different inhibition zone to Candida albicans, where the zone of inhibition showed that the F value of The zone of resistance to Candida albicans is greater than Ftable at the 0.05 (3.48) level and Ftable at the 0.01 (5.99) level, it can be concluded that the liquid feminine cleansing soap from tanjung leaf extract (Mimusp elengy l) 1% w/v, 3% w/v, and 5% w/v can inhibit Candida albicans.